The effects of electroacupuncture on rat sciatic nerve recovery. - Andraus, Rodrigo Antonio Carvalho; Sasaki, Mariana Fukuda; Silva, Murilo Paiola da; Santos, João Paulo Manfré dos; Fernandes, Karen Barros Parron; Oliveira, Rodrigo Franco de; Monte-Raso, Vanessa Vilela; Barbieri, Cláudio Henrique (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Acupuncture is an ancient form of treatment used initially in China and it is a currently common practice in the West among health professionals in various clinical conditions, causing local or remote biological responses. Objective: This experiment aims to evaluate the influence of electroacupuncture on recovery of peripheral nerve through functional gait analysis and nociception after crush injury in the sciatic nerve in rats. Methods: 30 Wistar rats were included, weighting 198g on average, which were divided into three groups. Functional analysis was performed by the method of Sciatic Functional Index (SFI) by shooting the rear footprints performed on a mat with controlled rate in the following days: preoperative; days 7, 14 and 21 post-operation. In the same days the animals were evaluated for nociception using von Frey filaments. Results: There was an improvement of the SFI in both treated groups compared with the control group. In the preoperative week there was no statistical difference (p> 0.05). In the 1st postoperative week there was statistical difference (p <0.05) when comparing the three groups. The 2nd week yielded the same characteristics of the first week (p <0.05). In the 3rd week there was a reversal of the improvement in groups, and the G2 achieved better rates (p <0.05) than G3 and G1, but G3 was better than G1. In the analysis of nociception there was no statistical difference (p> 0.05). Conclusion: The electroacupuncture in both treated groups accelerated and improved nerve recovery of the animals according to the SFI.